Using Tenggerese Oral Folktales for Teaching Paragraph Writing: How Good Are the Students’ Composition? - Sony Sukmawan; Lestari Setyowati (Yayasan Keluarga Guru Mandiri, 2022)
Indonesia is a nation that is rich in cultural artifacts. One of the cultural artifacts is the oral literature which is spread across the archipelago. This study is intended to describe the use of documented local Indonesian oral folktales applied for a paragraph writing class. The oral literature chosen was the Tenggerese oral literature in Pasuruan, East Java, Indonesia. The study used a mixed-method design. The subjects of the study were 46 students of the English Education Study Program who joined a paragraph writing class in Universitas PGRI Wiranegara, Pasuruan. The students’ writing was assessed by using a primary trait scoring rubric. The result shows that 98% of the students were able to make a topic sentence that shows comparison and contrast paragraphs. Although most of the students were able to make comparison and contrast paragraphs (83%), half of them were still unable to develop the ideas in the paragraph well (52%). The probable causes identified were first, the students were not given enough chance to revise and edit their composition, and secondly, the documented local oral literature lacked details in its story development. Yet, the study implies that local oral folklores have a chance to be used as one of the teaching materials for skill courses.